Image-D3.2 - Final Report On: Rock/Fluid Interactions At Supercritical Conditions - Ruggeri, Giovanni (Zenodo, 2015)
This report describes rock/fluid interactions at super-critical1 conditions building concepts for deep fluid circulation and validation from lab results (Deliverable D3.2 Rock/fluid interactions at supercritical conditions, pag. 14-15 of the DoW). In particular we report: • the results of fluid-rock interaction experiments by using a cold seal pressure vessel apparatus between aqueous solutions and crystalline solids in which several parameters were taken into account, such as type of solid, fluid composition and its salinity, solid/fluid ratio, P-T conditions. Fluids and solids were characterized before and after experiments. • Fluid-rock interaction modelling by using the modified code-packages upgraded up to supercritical conditions. • Collection and geochemical/isotopic analyses of fluid samples from geothermal systems in Iceland. • Validation of fluid-rock interaction modelling by comparing the results with the data of fluid from active geothermal fields. • Data interpretation and assessment of the mineralogical and chemical changes of the rocks and fluids by fluid-rock interaction of magmatic hydrothermal system around cooling intrusions at supercritical conditions as a function of temperature, pressure and fluid composition. : FP7